The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.4314/ahs.v15i4.21
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stigma and associated factors among people with epilepsy at Gondar University Hospital, Northwest Ethiopia: a cross-sectional institution based study

Abstract: Background: Epilepsy is the world's most common neurological disorder, affecting approximately 69 million people worldwide. Perceived stigma affects many domains of the lives of people with epilepsy. However, in Ethiopia there is dearth of study on perceived stigma specifically among people with epilepsy. Objective: To assess the prevalence of perceived stigma and associated factors among people with epilepsy (PWE) attending the outpatient department of the University of Gondar hospital, Northwest Ethiopia, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 24 publications
3
39
1
Order By: Relevance
“…There was an association between perceived stigma, socio‐demographic factors such as lower education, poor adherence to treatment and the duration of illness (Bifftu et al. ). Other studies reported similar findings (Pooe et al.…”
Section: Resultsmentioning
confidence: 99%
“…There was an association between perceived stigma, socio‐demographic factors such as lower education, poor adherence to treatment and the duration of illness (Bifftu et al. ). Other studies reported similar findings (Pooe et al.…”
Section: Resultsmentioning
confidence: 99%
“…Our screening for eligible articles resulted in 10 studies (20,(26)(27)(28)(29)(30)(31)(32)(33)(34), that assessed perceived stigma AND/OR the associated factors among 4016 people with epilepsy in the context of Ethiopia. All of the 10 studies were cross-sectional studies published between 2009 and 2018.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…All of the 10 studies were cross-sectional studies published between 2009 and 2018. Of these studies, three were conducted in Addis Ababa (28,29,32); the capital city of Ethiopia, another three were from Oromia regional state (20,33,34), two from Amhara regional state (27,30) and the remaining two from southern Ethiopia (SNNP) (26,31).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations